Room for improvement in breast milk feeding after very preterm birth in Europe: Results from the EPICE cohort - Wilson, E (2018)
Breast milk feeding (BMF) is associated with lower neonatal morbidity in the very preterm infant (<32 weeks gestation) and breastfeeding is beneficial for maternal health. Previous studies show large variations in BMF after very preterm birth and recognize the need for targeted breastfeeding support in the neonatal intensive care units (NICU). In a European collaboration project about evidence‐based practices after very preterm birth, we examined the association between maternal, obstetric, and infant clinical factors; neonatal and maternal care unit policies; and BMF at discharge from the NICU. In multivariable analyses, covariates associated with feeding at discharge were first investigated as predictors of any BMF and in further analysis as predictors of exclusive or partial BMF. Overall, 58% (3,826/6,592) of the infants received any BMF at discharge, but there were large variations between regions (range 36–80%). Primiparity, administration of antenatal corticosteroids, first enteral feed <24 hr after birth, and mother's own milk at first enteral feed were predictors positively associated with any BMF at discharge. Vaginal delivery, singleton birth, and receiving mother's own milk at first enteral feed were associated with exclusive BMF at discharge. Units with a Baby Friendly Hospital accreditation improved any BMF at discharge; units with protocols for BMF and units using donor milk had higher rates of exclusive BMF at discharge. This study suggests that there is a high potential for improving BMF through policies and support in the NICU.